Statin Usage Increases White Matter Hyperintensities: A Post Hoc Analysis of SPRINT-MIND. Issue 2 (23rd March 2023) - Goldstein, Eric D.; Garg, Gauri; Navarro, Kayla; Wolcott, Zoe; Yaghi, Shadi; Wong, Ka-Ho; McLean, Kaitlin; de Havenon, Adam H.
Abstract : Background: Progression of white matter hyperintensities (WMHs), a radiographic marker of cerebral small vessel disease, occurs with uncontrolled conventional cerebrovascular risk factors. Less certain, however, is the influence of dyslipidemia and the impact of 3-hydroxy-3-methylglutaryl-coenzyme-A reductase inhibitors (statins) on WMH progression. The goal of this study was to evaluate the influence of statins on the progression of WMH over a 4-year interval. Methods: We performed a post hoc analysis of the SPRINT-MIND database on those with serial volumetric WMH data. WMH progression was calculated as the difference in WMH volume between the 2 scans and then segmented into tertiles due to rightward skew. We defined statin usage as no therapy (0% of visits), partial therapy (1% to 99% of visits) or full therapy (100% of visits) as logged during study visits. Analysis of variance and χ 2 tests were used for continuous and categorical variables with adjustments made for variables known to influence WMH development. Results: A total of 425 individuals were included in this study: 53% without statins use, 27% partial use, and 20% full use. Demographic characteristics and baseline WMH volumes were similar among the cohort. Those with full statin use were significantly more likely to be in the top tertile of WMH progression (adjusted odds ratio: 2.30, 95% confidence interval: 1.11-4.77, P =0.025), despite improvement in dyslipidemia. Conclusions: SPRINT-MIND participants prescribed a statin were nearly 2.5 times more likely to be within the top tertile of WMH progression over 4 years, despite adjustment for synergistic risk factors and improvement in low-density lipoprotein.